Study of shear strength between laterite soil due to temperature influence based on laboratory scale - Saputro, Wira Hadi; Rusdiansyah, Rusdiansyah (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
South Kalimantan is a large wetland with an area of ​​382,272 hectares (ha). The condition of wetland with soft soil types in this area, especially peat soil can initiate fires during the dry season because the water content in the land decreases drastically. Moreover, fires that occur on peat soil land with road constructions do cause the temperature around the land to increase. The increment of this temperature can affect the physical and mechanical properties of the embankment/laterite soil. Therefore, this study aimed to determine the influence of hot temperatures on shear strength between laterite soils. The materials used were laterite soil samples from quarries in Banjarbaru, South Kalimantan, namely Mandiangin, Cempaka, and Landasan Ulin. The temperature variations applied below 100oC included 27, 50, 60, 70, 80, and 90oC. During the analysis, the method used was a direct shear test in the laboratory. Based on the study conducted, the data analysis results were obtained and presented in a graph. The results showed that the changes in characteristics of laterite soil were due to the influence of hot temperatures. Additionally, the outcome also signified that cohesion value (c) in Mandiangin, Cempaka, and Landasan Ulin laterite soils from a normal temperature of 27 to 90oC increased on average by 11.5, 19, and 53%. The analysis implied that when the soil water content decreased, most of the free water pumped out, leaving capillary water occupying the space between soil grains. Following the discussion, the value of internal friction angle (φ) of these laterite soils from 27 to 90oC increased on average by 60.5, 59.5, and 84%. The result showed that when the soil water content reduced and the pore water pressure decreased, increasing effective stress (σ’) in the soil. During the analysis, higher effective stress increased frictional resistance between soil grains, and φ value also improved. Therefore, soil mechanical properties parameters such as soil shear strength could be increased by adjusting soil temperature.